CONSIDERATIONS REGARDING THE DESIGN OF SPECIFIC TOURISM PRODUCTS FOR THE TOURISM DESTINATION ROMANIA - MONICA PAULA RAŢIU; AURELIA - FELICIA STĂNCIOIU; ANCA - DANIELA VLĂDOI; NICOLAE TEODORESCU (Annals of the University of Petrosani: Economics)
Romania, as tourism destination with its component micro-destinations (Muntenia, Oltenia, Banat - Crişana, Transylvania, Bucovina, Maramureş, Moldavia and Dobrogea), possesses many tourism attractions and at the same time has a real tourism potential. The fact that it is not included among the Europe’s „valuable” destinations represents a loss both for its inhabitants and for Europeans in general, too. One of the reasons is the lack of an image consolidated by identity elements or / and simply the lack of image that would represent the starting point for development of appropriate tourism products (developing a strategy). This paper proposes, starting from the image perceived by the inhabitants about their own destination – based on the example of Transylvania – to emphasize the importance and also the role of the destination image in developing the main directions of actions and, especially, in developing the strategy for the specific tourism products.